Proportional Thinking Levels of Eleventh Grade Female Students in Jordan - Miqdady , Ruba; Al-Quraan, Najah (Jordan Journal of Educational Sciences, 2017)
This study aimed to explore proportional thinking levels of eleventh grade female students in Jordan. This study also aimed to investigate the differences in proportional thinking due to: levels of mathematics achievement, and the academic stream, as well as the interaction between them. To acheieve the aim of the study, a pilot study was conducted to determine the types of proportional thinking of female students. Furthermore, a battery test was applied to a sample consisting of (523) students randomly chosen from all the eleventh grade female student at Al-Taibeh, Al-Wasteyah and Bani Obaid districts. Results showed the following percentages (25.05%, 60.04% , 14.53% , 0.38%) of female students classified as: very low , weak, intermediate, professional respectively. Results also showed that the proportional thinking levels differ according to the type of the secondary stream in favor of the scientific stream. However, they do not differ according to differences in achievement levels nor to the interaction between achievement levels and secondary stream in female proportional thinking